A three dimensional graphene/Pt catalyst fabricated by particle-constructing method and the catalytic activity for methanol oxidation. (26th November 2016) - Ji, Yucheng; Yu, Le; Hou, Min; Shen, Liming; Wang, Zhaoqun
Abstract: Graphene is an attractive catalyst support for direct methanol fuel cells (DMFCs). However, the close-packed structure and hydrophobicity of the graphene sheets will prevent noble metal nanoparticles (NMNPs) from exposed to the electrolyte, leading to a reduction in the utilization of NMNPs. In this work, a unique 3D graphene/PtNPs composite catalyst with double network channels is in-situ fabricated. The superficial rGO sheets of PS/rGO@PtNPs composite particles are interconnected to form 3D network structure due to the supporting of the PS microspheres. The 3D structure not only provides interconnected channel for diffusion of the electrolyte into the composite catalysts, but also forms an ideal graphene network to increase the connectivity and conductivity of the composite catalysts. Compared with the close-packed rGO/PtNPs catalyst, the PS/rGO@PtNPs composites with 3D network structure have higher catalytic activity, reaches up to 586.96 mA/mg for methanol oxidation reaction. Graphical abstract: Wrapping PS microspheres with graphene sheets, attaching PtNPs on the resultant PS/rGO composite particles to prepare PS/rGO@PtNPs composite particles, and finally constructing 3D ordered rGO/PtNPs network structure through in-situ self-deposition of the ternary composites, which evidently increased the catalytic activity in methanol oxidation reaction than the close-packed rGO/PtNPs composite. Highlights: In-situ fabricated three-dimensional graphene network. A facile and eco-friendly method via self-deposition of PS/rGO@PtNPs particles. Better conductive network and interconnective diffusion channel for electrolyte. Higher MO catalytic performance than closed-stacked rGO/Pt catalyst.